Online purchase intention: explorations of the Facebook users' psychological factors / Dilla Kartini Naradin ...[et al.] - Kartini Naradin, Dilla; Hairuddin, Hanitahaiza; Ab Malik, Ariff Md; Suzila Kassim, Erne (UiTM Press, 2018)
The social media usage in this era is not only for communication with others, but also as a platform for many businesses to promote and sell their product online. Facebook is one of the biggest social media network among marketers due to the innovativeness and effectiveness after the existence of e-commerce. Therefore, this study aims to examine the relationship between the psychological factors of Facebook; trust, privacy and security and online purchase intention. 396 Malaysian Facebook users were involved in this study by using purposive and convenience sampling method. The findings show that Trust, Privacy and Security have positive significant relationships with the Online Purchase Intention while the Security has the strongest significant impact on Online Purchase Intention. This study provides an understanding of how to develop strategies to engage with Facebook users. By engaging in the sharing of information with consumers the marketing approach can be implemented effectively.